A Big Apple for Educators: New York City's Experiment with Schoolwide Performance Bonuses Final Evaluation Report - Marsh, Julie A. (RAND Corporation, 2011)
For three school years, from 2007 to 2010, about 200 high-needs New York City public schools participated in the Schoolwide Performance Bonus Program, whose broad objective was to improve student performance through school-based financial incentives. An independent analysis of test scores, surveys, and interviews found that the program did not improve student achievement, perhaps because it did not motivate change in educator behavior.